Samomorilne misli pri bolnikih z rakom - Medjedović, Sabina (Obzornik zdravstvene nege, 2025)
Introduction: Cancer patients have a higher risk of suicidal ideation and suicidality than the general population, so understanding emotional distress and recognising suicidal ideation in cancer patients is of paramount importance. The aim of this literature review is to examine the current state of research on suicidal ideation in cancer patients.Methods. The literature review process is illustrated in the PRISMA diagram. Nine studies were included in the review. The research method comprised content pooling and comparison of the results of the studies included in the literature review.Results: Our results indicate that suicidal ideation is present in 11% to 26% of oncology patients and that screening tools are available for identifying this problem. However, these screening tools are not routinely used in clinical practice. The most commonly used screening instruments are the Distress Thermometer and the PHQ-9 Health Questionnaire. The presence of suicidal ideation is recognised more quickly in facilities where health care professionals use screening instruments.Discussion and conclusion: The results show that suicidal ideation is present in oncology patients and that various screening tools are available for its detection. Regular use of screening tools is needed, along with recognition of emotional distress as the sixth vital sign. Healthcare professionals require motivation and training through workshops on the importance and strategies for effective management of emotional distress in cancer patients
Keywords: cancer; oncology; onkologija; rak; samomomor; samomorilne misli; suicidal ideation; suicide